A descriptive analysis of anglicisms used in ecuadorian magazines - Carrión Mogrovejo, Javier Fernando (2010)
This research is about the DESCRIPTIVE ANALYSIS OF ANGLICISMS IN ECUADORIAN MAGAZINES. This study is based in Ecuadorian magazines printed in 2010 to understand the actual influence of the Anglicisms in the Ecuadorian magazines. To achieve this study, I took into the variables such as: cultural magazine, scholarly magazine, and general interest magazine. This research is a descriptive analysis, to gather the scientific material necessary for the theoretical frame, I have used the bibliographic method; and the Descriptive-analytic methods in order to do the descriptive and statistical analysis and the interpretation of the data gathered through the field research. The strategies were: selection of Ecuadorian magazines printed in 2010, Anglicisms searching in the magazines, marking and researching if the words selected are or not an Anglicism through of a dictionary or Web. This investigation has allowed to see that the Anglicisms found in the scripts, articles, reports, essays, and general data issued by jouwœrnalists, reporters, editors, writers, and experts in science and technology influence a great deal in the Spanish language usage of the Ecuadorian readers.